Pulmonary arteriovenous malformation with unexplained cyanosis as the first presentation of hereditary haemorrhagic telangiectasia, case report, and literature review. Issue 7 (22nd July 2021) - Alakhfash, Ali; Alqwaiee, Abdullah; Almesned, Abdulrahman; Al-Hassnan, Zuhair N
Abstract: Background: Pulmonary arteriovenous malformations (PAVMs) are rare pulmonary vascular anomalies. They can result in right-to-left shunt and, if significant, low systemic saturation, cyanosis, polycythaemia, and paradoxical systemic embolization. Case summary: Eighteen months old female child was referred to our centre due to unexplained central and peripheral cyanosis. Based on the agitated saline contrast echocardiography study, computed tomography scan confirmed the presence of abnormal vasculature at the left lower lobe. Percutaneous closure of the PAVM was performed using Amplatzer Duct Occluder type 1 device. The genetic study revealed a pathogenic mutation in the endoglin gene, which is a known cause of hereditary haemorrhagic telangiectasia (HHT) inhered in an autosomal dominance pattern. Discussion: PAVM could be the first manifestation of HHT. Closing the malformation percutaneously is feasible, which can eliminate the right to left shunt and improves the saturation. Genetic study is warranted in these cases, as well as long-term follow-up.